2022
DOI: 10.1186/s12917-022-03194-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylazine, detomidine, medetomidine and dexmedetomidine during laparoscopic SCNT embryo transfer on pregnancy rate and some physiological variables in goats

Abstract: Background The present study was conducted to determine if using α2-adrenergic agonists results in decreased stress levels (lower cortisol levels) in goats used for laparoscopic embryo [somatic cell nuclear transfer (SCNT)] transfer; and there is an effect on pregnancy rate when stress levels are lessened. Sixty healthy does aged 24 ± 4 months and weighing 30 ± 3 kg were used in experimental, prospective, randomized and blinded study. In this study, embryos were obtained by the Somatic Cell Nuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
3
4
0
Order By: Relevance
“…On the contrary Kutter et al, 2006 stated that there is a significant reduction in respiratory rate between 5-30 minutes after administration, furthermore, these drugs has a significant decrease in heart rate up to 60 minutes after injection. On the other hand the results of this work coincide with Kutter et al, 2006Aghamiri et al, 2022 who stated that the animals restore ruminal motility, appetite and the attitude of urination and defecation within 120 minutes after administration of the anesthetic protocol. The results of this article stated that the satisfactory visualization and manipulation of the internal viscera was achieved through pneumoperitoneim through insufflation of Co2 as well as the dorsal recumbency with Trendelenburg position by 20 degree.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…On the contrary Kutter et al, 2006 stated that there is a significant reduction in respiratory rate between 5-30 minutes after administration, furthermore, these drugs has a significant decrease in heart rate up to 60 minutes after injection. On the other hand the results of this work coincide with Kutter et al, 2006Aghamiri et al, 2022 who stated that the animals restore ruminal motility, appetite and the attitude of urination and defecation within 120 minutes after administration of the anesthetic protocol. The results of this article stated that the satisfactory visualization and manipulation of the internal viscera was achieved through pneumoperitoneim through insufflation of Co2 as well as the dorsal recumbency with Trendelenburg position by 20 degree.…”
Section: Resultssupporting
confidence: 87%
“…While significant decrease in respiratory rate was recorded between 10-20 minutes after anesthetic induction. This come in contact with that reported by Aghamiri et al, 2022 Who mentioned that the balanced anesthetic regimen involved the combination of xylazine, ketamine and propofol anesthetic drugs to achieve total intravenous general anesthesia with minimal negative effect of individual drugs on the cardiopulmonary function. On the contrary Kutter et al, 2006 stated that there is a significant reduction in respiratory rate between 5-30 minutes after administration, furthermore, these drugs has a significant decrease in heart rate up to 60 minutes after injection.…”
Section: Resultssupporting
confidence: 59%
“…In addition, the reverse responses of CORT (increase) and CHE (decrease) to TA supplementation were noticed, supported by a prior study in which CHE inhibition induced the elevation of CORT level ( 49 ). Further, the higher level of CORT in TAL could reflect an escalated degree of stress ( 50 ), and the lower GR concentration in TAH might imply the decrease of antioxidative ability ( 51 ). Adding TA at 0.6% of DM raised the total antioxidant T-AOC in this trial, which was consistent with the finding of Yang et al ( 5 ) that the plasma T-AOC was increased by the inclusion of 0.65, 1.3, and 2.6% TA.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Aghamiri et al (2022), the effects of xylazine, detomidine, medetomidine and dexmedetomidine were investigated during laparoscopic SCNT embryo transfer on pregnancy rate and some physiological variables in goats. Their findings revealed that serum cortisol concentration significantly decreased in the α2-adrenergic agonists groups at the time points of 45 and 60 min (Aghamiri et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Aghamiri et al (2022), the effects of xylazine, detomidine, medetomidine and dexmedetomidine were investigated during laparoscopic SCNT embryo transfer on pregnancy rate and some physiological variables in goats. Their findings revealed that serum cortisol concentration significantly decreased in the α2-adrenergic agonists groups at the time points of 45 and 60 min (Aghamiri et al, 2022). In another paper, the level of cortisol in a detomidine-administered cattle was evaluated, where the authors found that in all groups, the level of plasma cortisol declined (Gnanasekar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%